FN1 from cancer-associated fibroblasts orchestrates pancreatic cancer metastasis via integrin-PI3K/AKT signaling - Zhu, Xianguang; Li, Yanwei; Liu, Huifang; Xiao, Zheng (Frontiers in Oncology, 2025)
ObjectiveThe metastasis of pancreatic ductal adenocarcinoma (PDAC) is closely linked to the remodeling of cancer-associated fibroblasts (CAFs) within the tumor microenvironment (TME), though the precise molecular mechanisms remain unclear. This study aims to elucidate the role of CAFs in PDAC metastasis.MethodsWe integrated transcriptomic (GSE183795) and single-cell sequencing data (GSE156405) to screen for core genes associated with PDAC. In vitro co-culture models, functional assays (Transwell migration, Western blotting, qRT-PCR), and clinical data analysis were employed.ResultsMulti-omics analysis identified FN1 as a pivotal hub gene in the PI3K pathway, highly expressed in metastatic CAF subsets. In vitro experiments confirmed that FN1 activates the PI3K/AKT pathway through integrin receptors, influencing cell invasion and the immune microenvironment. Combined inhibition of the PI3K/AKT pathway and integrins synergistically suppressed tumor invasion. Clinical data showed that high FN1 expression correlated with shortened patient survival and an immunosuppressive microenvironment (M2 macrophage/Treg cell infiltration).ConclusionFN1 directly drives PDAC metastasis via the integrin-PI3K/AKT axis and indirectly promotes a “cold tumor” microenvironment by recruiting immunosuppressive cells. This dual role of FN1 enhances our understanding of CAFs heterogeneity and offers novel therapeutic strategies for PDAC.